Analisis Hubungan Antara Teknologi Informasi, Kooperasi Organisasi Terhadap Kinerja Rantai Pasok pada Perusahaan Konstruksi Menengah di Jakarta - Hasibuan, Muhammad Akbar; Fathurahman, Heri (Syntax Literate, 2025)
Based on data from the Central Statistics Agency (BPS), the number of construction companies in Indonesia was 197,030 units in 2022. The number was corrected by 3.13% compared to the previous year which reached 203,403 units. In the construction industry, the supply chain is a coordinated and cooperative system consisting of various parties, which contribute to the overall course of the project to achieve project goals in producing construction products. This study uses a quantitative approach by distributing questionnaires via Google Form to 120 respondents who work as leaders of medium-sized construction companies in Jakarta. By using SPSS, descriptive statistical analysis and inferential statistics were obtained using regression testing. The results showed that in the sample of medium-sized construction companies in Jakarta: a) there is a relationship between Communication Methods and Use Integrated Information Technology with Interfunctional Cooperation; b) there is a relationship between Interfunctional Cooperation and Communication Methods with Interorganizational Cooperation; c) there is a relationship between Interfunctional Cooperation and Interorganizational Cooperation with Supply Chain Performance Outcome.